PEMBOBOTAN PARAMETER DENGAN PAIRWISE COMPARISON PADA CASE BASED REASONING PENYAKIT TANAMAN ANGGREK MENGGUNAKAN ALGORITMA SIMILARITAS KNN BERBOBOT - Andin fatchul muin jauhari Andin (Universitas Muhammadiyah Purworejo, 2021)
Nowadays, orchid farmers or hobbyists are starting to increase, because the diversity of the unique flowers and their rarity has attracted farmers and plant hobbyists. Lots of people want this beautiful plant, but caring for this orchid plant is not easy, it requires high accuracy, so that orchid plants do not die from disease. When orchid plants are attacked by a disease, orchid farmers and hobbyists need consultation about diseases that attack orchid plants, but experts or orchid plant extension agents are relatively difficult to find. Based on this, farmers and hobbyists need a system or application that can be accessed anytime and anywhere. An expert system is the right answer to make it easier to conduct consultations without having to visit an orchid plant expert. To provide information about how to diagnose types of diseases and how to deal with orchid plant diseases, an expert system application that can represent an expert in their field is needed to provide solutions to orchid plant disease problems using the pairwise comparison method and the KNN similarity algorithm. Pairwise comparison method on case-based reasoning of orchid plant disease produced weights with 3 categories of symptoms, namely mild symptoms with a weight of 0.09, moderate symptoms with a weight of 0.24 and severe symptoms with a weight of 0.67. Weighting parameters with pairwise comparison on case-based reasoning of orchid plant disease using the weighted KNN similarity algorithm will recommend several diseases with similarity above 0.5 and diseases with similarity below 0.5 will be entered into the revise table to find a solution.